Work-related injury and disease in Australian road transport workers: A retrospective population based cohort study. (March 2019) - Xia, Ting; Iles, Ross; Newnam, Sharon; Lubman, Dan I.; Collie, Alex
Highlights: This study examined a range of different work-related injury and disease in transport sector workers across different driver groups by using a population-based data at a national level for workforce injury. This study provides evidence of a high rate of work-related injury and disease among transport workers. Truck drivers and other drivers are at increased risk of musculoskeletal injury rooted in the transportation environment, whilst public transport drivers are more likely to experience occupational mental stress. The median duration of time loss due to work-related injury and illness was longer in automobile drivers and truck drivers compared to other occupations.